Combination therapy in a large lower lip mucocele: A non-invasive recommended technique - Hamed Mortazavi; Maryam Baharvand; Somayeh Alirezaei; Robab Noor-Mohammadi (Wolters Kluwer Medknow Publications, 2014)
Introduction: Salivary mucocele is a common benign lesion of the oral cavity, usually presented as a single bluish lesion caused by trauma to the minor salivary gland ducts. We aimed to describe a new combination therapy (micromarsupialization plus intralesional corticosteroid injection) to treat a large mucocele on the lower lip. Case Report: We administered three intralesional dexamethasone (8 mg/2 ml) shots along with standard silk sutures in one-week intervals on a large labial mucocele (primary size: 3.5 cm Χ 1.5 cm) of a 26-year-old man over a three-week duration. Complete healing was obtained three weeks after treatment. A six-month follow-up revealed no signs of recurrence or complications. Discussion: Combination of intralesional dexamethasone and micromarsupialization leads to complete healing of a large lower lip mucocele, and can be considered as an alternative therapeutic method to conventional surgery.